2023
DOI: 10.32996/jlds.2023.3.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Learning English by Kindergarten Children in Saudi Arabia: A Mothers’ Perspective

Abstract: In an era where the English language has become dominant in all fields and is the prevailing language worldwide, many Arab parents and intellectuals are wondering about the optimal age to start teaching their children English. Should they speak to their children in English at an early age? Should they enrol their children in a pre-school that teaches English only? What is the effect of teaching English to children in kindergarten on their learning of Arabic and their academic achievement in later stages? This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
1
0
1
Order By: Relevance
“…This is in line with opinion [15]that Typically, second-language learning becomes more difficult for the 15-or 20 -years -old than 5 -or 10 -years old. Not much different from the research results [16] that The results of interviews with a sample of 300 mothers representing all segments of society showed that 70% of the mothers believed that the best age to teach children English was between four and five years old. Furthermore, [17]reveals the importance of early language learning has been specified by the European Commission's (EC) Action Plan 2004-2006 which recommends learning one foreign language (FL) from an early age and the introduction of a second FL by the end of primary school.…”
Section: The Urgency Of Early Childhood English Language Learning In ...contrasting
confidence: 90%
See 1 more Smart Citation
“…This is in line with opinion [15]that Typically, second-language learning becomes more difficult for the 15-or 20 -years -old than 5 -or 10 -years old. Not much different from the research results [16] that The results of interviews with a sample of 300 mothers representing all segments of society showed that 70% of the mothers believed that the best age to teach children English was between four and five years old. Furthermore, [17]reveals the importance of early language learning has been specified by the European Commission's (EC) Action Plan 2004-2006 which recommends learning one foreign language (FL) from an early age and the introduction of a second FL by the end of primary school.…”
Section: The Urgency Of Early Childhood English Language Learning In ...contrasting
confidence: 90%
“…This is the reason why many parents prefer ECE institutions with excellent English language programs. Similar things are also found in research results that 70% prefer to enroll their children in a kindergarten that teaches English [16]. Furthermore, early knowledge of English also supports children to be better prepared for the era of digitalization in their daily lives.…”
Section: "It Is Important To Train Children's Sensitivity In the Engl...supporting
confidence: 80%